Internacionalização da educação superior: estratégias e ações da Universidade Tecnológica Federal do Paraná - Tavares, Marcelo (2016)
The present dissertation is inserted in the internationalization of the university-level education research field and aimed to analyze the strategies and internationalization actions of the Universidade Tecnológica Federal do Paraná (UTFPR), locus of research. The study sought to establish the current context in which the internationalization is inserted and contextualize the research problematic presenting definitions, concepts, reasons and strategies linked to an international dimension. It also presents a historical context of the internationalization of Brazil and current public policies related to this topic. This research used content analysis to analyze institutional documents (Institutional Development Plans (2004-2017) and Management Reports (2000-2014)); semi-structured interviews (Director of International Relations, Coordinator of programs and actions related to the mobility of students, Head of the Department of Education and Dean of Research and Graduate Studies); information pertaining to the theme from the university’s website and events held in the Campus of the institution. Data were analyzed using the procedures prescribed for this type of analysis with the establishment of three categories: concepts, strategies and actions. Based on the foregoing, in terms of synthesis, could be understood that increasing the participation of UTFPR on the international scene has always been linked to the institution’s policies and goals, yet without an political institutional plan without objectives, strategies and goals established systematically. In the case of the conception of the internationalization of UTFPR it was realized that the theme currently gained more focus and greater coverage in the institution. In this context, Ciência Sem Fronteiras program contributed to, giving greater visibility to UTFPR on the world stage. From then on, specific strategies and actions are being developed in seeking internationalization under institutional perspective, of the servers, the expansion of mobility, and greater visibility of the institution in the international arena, regional integration and promotion of internationalization at the university. Overall, the management of internationalization in the institution does not have a formal project, but has specific strategies and actions seeking their expansion. Thus, the process of internationalization in UTFPR presents itself in an early stage, with strategies and actions seeking to expand the international dimension in the institution who takes singular importance to its expansion and consolidation.